School counselors’ perceptions of virtual counseling in Lebanon: A qualitative study - Jaber, Fatima; Al-Hroub, Anies (Frontiers in Psychology, 2023)
Virtual counseling has become an increased necessity as a result of the current pandemic as well as the need for methods that comply with the continuous changes and advancements. Studies conducted have shown that the perceptions of counselors of the benefits and barriers reflect whether or not the counseling service will be successful. This study is a descriptive research design following a qualitative approach. The study aimed to explore (a) the school counselor’s perceptions of the benefits and barriers they encounter when using virtual counseling, (b) the perceived differences between conducting virtual counseling and in-person counseling; and (c) whether participation in virtual counseling differ as a result of students’ characteristics in the perception of school counselors. Five private schools in the Beirut region were contacted as they were known to have virtual counseling programs. Both the schools and counselors were purposively chosen. Seven in-depth semi-structured interviews and one focus group discussion were conducted with the participants. Interpretational analysis was carried out to assess and analyze the obtained data. The results showed that through these experiences counselors were able to develop new methods related to technology and other practices to limit the effects of obstacles. Counselors’ communication tools were also fine-tuned since they had to rely on unorthodox methods to understand students and deal with them better. Results showed that the benefits also have to do with time and method flexibility, the main barriers were issues of privacy, change in workplace dynamics, and lack of usage of tools. The findings were discussed in relation to four main themes: (a) service delivery adaptation, (b) working with technology, (c) counselor’s practices in delivering virtual counseling, and (d) preparation and training for virtual counseling. Being that it is qualitative research; the interpretational analysis was carried out to assess the obtained data. The results showed that the main benefits have to do with time and method flexibility, the main barriers were issues of privacy and change in workplace dynamics. The results showed that the new changes, the counselor’s experience, along with personal attributes of counselors and students all influenced the efficiency of the counseling sessions.